Nature, nationalism and neoliberalism on food packaging: The case of Sweden. (April 2020) - Andersson, Helen
Abstract: Scholars have shown that representations of nature are common on food packaging, often to sell products that are far from natural. They have also shown that brands can add value to products using nationalist messages. However, much less research has gone into how these representations take form in specific national settings. In this article, using multimodal critical discourse analysis, I investigate a sample of Swedish food packaging, and show how the nature represented evokes associations established systematically by governments building up nationalist imagery associated with social democracy, openness, freedom, responsibility, equality and fairness. I argue that at a time when Sweden is moving to the right politically, becoming a model neoliberal society, such representations, used for marketing purposes, help communicate a banal sense that Sweden is very much as it always has been.